Dinamika Organisasi Muhammadiyah di Denpasar dalam Perspektif Sejarah 1998-2018 - Sari, Widia Puspita; Ardhana, I Ketut; Tagel Eddy, I Wayan (Humanis; Vol 24 No 3 (2020), 2020)
This research discussed about the dynamics of Muhammadiyah Organization in Denpasar in the Hitorical Prespektive 1998-2018. The formulation of the problems are 1) How the activities of the Muhammadiyah Denpasar Area in religius Ideology 2) How are the views of the Muhammadiyah Denpasar Area towards members who are involved in politic 3) How are the the views of the citizens toward the Muhammadiyah Denpasar Area. In this research use historical methodology is oral history and political history. The analysis uses explanation theory, symbolic interactionalism and multicultural theory. The result is Muhammadiyah activities ini Denpasar in religion and politic. The final research find about Muhammadiyah in Denpasar recently not only enganged in religion but also partisipate in politic.